2020
DOI: 10.1108/ijotb-03-2019-0041
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of key predictors of organizational citizenship behavior of civil servants

Abstract: PurposeThe purpose of this paper is to examine the key predictors of organizational citizenship behavior of civil servants in local governments in Uganda.Design/methodology/approachThe study draws on a quantitative approach and cross-sectional survey design. Data were collected using a self-administered closed-ended questionnaire from a sample size of 265 respondents derived using Krejcie and Morgan (1970) from a population of 844 civil servants using stratified simple random sampling technique. Data were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
2
6
0
Order By: Relevance
“…Accordingly, AC is found to be positively related to both dimensions of OCB. The findings were consistent with Hasani et al (2013) and Obedgiu et al (2020). Besides, our findings support the assertion of Cohen and Liu (2009), which emphasized the relevance of AC in the OC-OCB relationship.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Accordingly, AC is found to be positively related to both dimensions of OCB. The findings were consistent with Hasani et al (2013) and Obedgiu et al (2020). Besides, our findings support the assertion of Cohen and Liu (2009), which emphasized the relevance of AC in the OC-OCB relationship.…”
Section: Discussionsupporting
confidence: 92%
“…Existing findings indicate that AC is positively associated with OCB (Khaola & Rambe, 2021;Obedgiu et al, 2020;Khaskheli et al, 2020). Specifically, AC causes an increase in employee job satisfaction, which is positively related to both OCB dimensions.…”
Section: Affective Commitment (Ac) and Organizational Citizenship Beh...mentioning
confidence: 98%
“…For instance, Moorman (1991) observed the positive impact of organizational justice on organizational citizenship behaviour, during his study among the organizations in the United States. But when Jehanzeb and Mohanty (2019) and Obedgiu et al (2020) repeated the same research in the banking industry in Pakistan and civil servants in Uganda respectively, they found an insignificant relationship between the two variables. There is a genuine need to examine organizational justice and its influence on various work attitudes, such as organizational citizenship behaviour (Hameed et al, 2019).…”
Section: Introductionmentioning
confidence: 87%
“…Organ (1988) observed that OCB consists of five vital constituents such as altruism, civic virtue, courtesy, sportsmanship and conscientiousness. OCB makes a prominent contribution to the efficiency and effectiveness of the organization by improving the productivity of the workforce, equipping the organization to meet various environmental changes, and solidifying better inter and intra workgroup coordination (Obedgiu et al, 2020). Even though these extra-role behaviours induce a positive work attitude and environment, there is no obligation on the part of employees to exhibit such behaviours simultaneously with their in-role behaviours (Ramdeo and Singh, 2019).…”
Section: Organizational Citizenship Behaviour (Ocb)mentioning
confidence: 99%
See 1 more Smart Citation